Partnership, inclusion and innovation in occupational therapy: Essential or optional ingredients to flourish in a changing environment?. (5th December 2017) - Gilbert Hunt, Susan
Abstract : Background/aim: Historically occupational therapy has evidenced a tenacity to adjust and adapt to societal changes. Currently in Australia we are in the midst of significant change in health, disability and aged care service delivery alongside increasing numbers of new graduates seeking employment. Both of these changes create challenges and opportunities for the profession. How the profession adjusts to new service delivery models and supports new graduates in this changing work environment will influence our future. Methods: Using examples from practice the paper explores ways in which partnership, inclusion and innovation can be effective in a changing environment. Results: Doing effective partnership takes time, energy and a shared commitment of all involved and often requires negotiations and compromise. Inclusion can be tricky and requires vigilance and ongoing reflection on actions to determine if the outcomes are what was intended. Innovation can play two roles; it can be used to conserve current practice in new ways or it can offer agency to disrupt and redefine practice. Conclusion: The way in which the profession chooses to enact partnerships and inclusion will play a vital role in shaping the future. Similarly the space and support made for conservative or disruptive innovation will determine how we choose to define ourselves going forward. Moreover, these choices and actions will govern how effective we are in navigating the changing environment and supporting new graduates transitioning into the profession.